Pendampingan Masyarakat dalam Merehabilitasi Tanaman Kakao dengan Menggunakan Teknologi Sambung Pucuk - Susiyanti, Lusia Ina; Wahyuni, Yuyun; Jeksen, Julianus (LPPM Universitas Flores, 2023)
Plea Puli is a cocoa production centre located in Nita District, Sikka Regency, East Nusa Tenggara Province. KSU is a farmer group institution its main activities are crop farming, plantation commodities and animal husbandry until now has several business units, including joint business units, savings and loans, agricultural business units, food granary business units and cocoa commodity joint marketing business units. Currently, cocoa production is constrained because the plants are old and attacked by pests. Efforts that can be made to improve cocoa production are by rehabilitating plants. Rehabilitation can be done by the shoot connection method. Shoot splicing is one technique to propagate plants using scion and rootstock. The scion used must meet several criteria, namely the plant is not attacked by pests and diseases, comes from superior clones and is resistant to pest and disease attacks. Tools and materials: pruning scissors, grafting knife, plastic lid, entres. The activity began on August 12 - December 5, 2023, and was carried out in Bloro Village, Nita District, methods: Observation methods, interviews and literature reviews. Shoot splicing is carried out on water shoots aged 2-3 months, spliced shoots have a distance of 15-30 cm from below the soil surface, stems are large and are not attacked by pests and diseases. The entries used are brownish-green entries. Water shoots are cut by separating 5-6 leaves, then the rootstock is split in the middle evenly with the left and right incisions. The entry is cut by separating 2-3 buds, then inserting the entry in the joint tread and tie, after which the plastic is covered on the entry that has been knotted and tied. The results of the connection can be seen in 2-3 weeks, the connection is said to be successful if shoots appear. Sufficient knowledge and skills are needed in connecting so that it can be produced.